2023
DOI: 10.2147/jmdh.s412398
|View full text |Cite
|
Sign up to set email alerts
|

Low Trend for VZV-Associated Disease Patients to Visit Neurologists

Abstract: Background Herpes zoster (HZ) is a skin disease that can also cause virus-infectious peripheral neuropathies. Despite this, there is limited information on patient preferences for seeking medical attention for HZ and zoster-associated pain (ZAP). Our study aimed to evaluate how frequently patients with ZAP choose to visit neurologists for their symptoms. Methods This study conducted a retrospective review of electronic health records in three general hospitals from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 99 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…A previous study conducted in China reported that patients with HZ, PHN, and zoster-associated pain primarily visited dermatology and pain management specialists. 41 Neurologist consultations were more important in severe cases of HZ, where neuropathic zoster-associated pain and PHN cause extensive nerve injuries (e.g., VZV vasculitis). 41 As neurologists are not frequently involved in the management of HZ cases and assessment of vaccinations, they were not interviewed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study conducted in China reported that patients with HZ, PHN, and zoster-associated pain primarily visited dermatology and pain management specialists. 41 Neurologist consultations were more important in severe cases of HZ, where neuropathic zoster-associated pain and PHN cause extensive nerve injuries (e.g., VZV vasculitis). 41 As neurologists are not frequently involved in the management of HZ cases and assessment of vaccinations, they were not interviewed in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Neurologist consultations were more important in severe cases of HZ, where neuropathic zoster-associated pain and PHN cause extensive nerve injuries (e.g., VZV vasculitis). 41 As neurologists are not frequently involved in the management of HZ cases and assessment of vaccinations, they were not interviewed in this study.…”
Section: Discussionmentioning
confidence: 99%